When I think of you - Ariel, Myah (Berkley Romance, 2024)
"In this sweeping second chance romance from debut author Myah Ariel, the unexpected spark of two former flames may force them to choose between their dreams and each other. Kaliya Wilson has paid her dues. But all the years behind the reception desk at a flashy film studio have only pushed her movie-making dreams further out of reach. That is, until a surprise reunion presents an opportunity that could make her career, or break her heart...a second time. It's been seven years since Kaliya's whirlwind college romance with Danny Prescott went up in flames. While her passions have stalled, his career is taking off. So when the hot shot director reappears to offer her a job on his next production, it's a shock to the system. Working with Danny may recapture the intensity of their film school days, but trusting him again won't come as easily. As the pair allows themselves the openness and vulnerability to entrust their deepest truths to each other, the possibility of a true connection draws ever closer. But when Hollywood politics and scandal threaten to sink the production and her career, Kaliya may have to risk everything to do what's right-even if it means letting go of the second chance love of a lifetime"--